Hemispheric surgery for severe epilepsy in early childhood: a case series. Issue 4 (17th August 2021) - Pacetti, Mattia; Giacomini, Thea; Cossu, Massimo; Russo, Giorgio Lo; Prato, Giulia; Morana, Giovanni; Tortora, Domenico; d'Orio, Piergiorgio; Lodi, Monica; Casellato, Susanna; Scarpa, Pina; Cama, Armando; et al.
Abstract: Objective : Hemispheric surgery is an effective and cost‐effective option for hemispheric epilepsy. Data specifically focusing on very early infancy are scant. In our study, we report the results of hemispheric surgery in children under three years of age, along with clinical, neuroradiological and EEG features, from two Italian epilepsy surgery centres. Methods : After reviewing our epilepsy surgery databases (2008‐2018), we identified 14 patients (seven males) submitted to hemispheric surgery, under three years (range: 2‐29 months), with a follow‐up of at least 12 months. Results : No deaths occurred, and surgical complications were observed in 3/17 procedures. At final follow‐up visit (mean: 30.8 months; range: 12‐90), 10/14 patients (71.4%) achieved Engel Class I (eight Class 1A, one Class 1B, and one Class 1C). Antiepileptic drugs were completely discontinued in three and reduced in eight, thus a significant decrease in drug regimen after surgery was achieved in 11/14 patients (78.6%). Before surgery, severe developmental delay was present in 10 patients, moderate in two and mild in two. At the last follow‐up visit, the degree of developmental delay changed from severe to moderate in five patients, remained unchanged in six cases (four severe and two moderate), and changed from mild to moderate in two following surgery. Significance : In many cases, hemispheric surgery in children under three years is effective in achieving seizure freedom or reducing seizure frequency, with the possibility of simplifying complex drug regimens. Moreover, it appears to be a safe and well tolerated procedure, leading to improvement in cognition and posture.